Efficiency of herbicides of different modes of action for the control of Conyza sumatrensis in post-harvest corn (Bioagro, 2024)
After the indiscriminate use of glyphosate to control weeds in areas of agricultural cultivation, biotypes of Conyza spp. resistant to the product, making it difficult to control. The objective of the work was to analyze the efficiency of systemic herbicides with sequential application of contact herbicides for the control of Conyza sumatrensis in post-harvest corn. A randomized complete block design was used with a factorial arrangement, with factor A being systemic herbicides (halauxifen-methyl+diclosulam+glyphosate; 2,4 D+glyphosate; triclopyr+glyphosate) and Factor B contact herbicides (without herbicide of contact; glufosinate ammonium; saflufenacil). The application of systemic herbicides was carried out after the maize harvest and after 10 days, the sequential application of contact herbicides. The variables evaluated were regrowth percentage at 28, 35 and 42 days and control percentage at 14, 21, 28, 35 and 42 days. For the regrowth percentage variable, interaction of factors was observed on the 3 dates evaluated, the weeds that received the sequential application of contact herbicides did not show regrowth. In relation to the control percentage, interaction between the factors was also recorded for the five evaluation dates, all the weeds that received the sequential application of contact herbicides, from 28 days, presented high control percentages (between 98.5% and 100%). Systemic herbicides with sequential application of contact herbicides used in this experiment are effective in controlling C. sumatrensis.
Keywords: Contact herbicides; sequential application; systemic herbicides